The Synergy of Penta Helix Plus in Reclamation Activities (A Study on Mining Strategy in the Regency of Pasuruan) - Munir, Misbahul; Bisri, Mohammad; Hakim, Luchman; Putra, Fadillah (Journal of Indonesian Tourism and Development Studies, 2023)
Penta Helix is used in public policy, but in some instances, the Penta Helix can be used as a standard for implementing restoration activities. The involvement of the Penta Helix Plus actor is vital to oversee mining activities and, at the same time, make restoration activities successful in mining.  This research method uses a mixed method, namely combining qualitative data in the form of interviews, documentation, and observations with quantitative data in the form of questionnaires, then conclusions are drawn. This research shows that the Penta Helix Plus is an alternative that involves many parties and becomes an ideal new pattern. Hypothesis testing was obtained at 2p = 0.90 in the rejection area of Ho. In addition, the role of Penta Helix Plus shows that entrepreneurs are much more dominant, with 29%, which shows the restoration of the PT. HMM is based on a high level of personal awareness. In addition, environmental sensitivity that must be returned to its original state is also the reason for this restoration. This study concludes that the median test results show the synergy between the Penta helix plus actors in the restoration activities of excavation C in Pasuruan. Penta Helix Plus is an offer for a new formulation as well as public participation in synergy in controlling exploitation activities and expecting restoration activities to be carried out. The involvement of the Penta Helix Plus cannot be separated from the elements of communication and coordination, which are the most critical synergy indicators. Key Words: Mining, Penta helix plus, reclamation.